Manipulating T-cell metabolism to enhance immunotherapy in solid tumor - Chen, Chen; Wang, Zehua; Ding, Yi; Qin, Yanru (Frontiers in Immunology, 2022)
Cellular metabolism is not only essential for tumor cells to sustain their rapid growth and proliferation, but also crucial to maintain T cell fitness and robust immunity. Dysregulated metabolism has been recognized as a hallmark of cancer, which provides survival advantages for tumor cells under stress conditions. Also, emerging evidence suggests that metabolic reprogramming impacts the activation, differentiation, function, and exhaustion of T cells. Normal stimulation of resting T cells promotes the conversion of catabolic and oxidative metabolism to aerobic glycolysis in effector T cells, and subsequently back to oxidative metabolism in memory T cells. These metabolic transitions profoundly affect the trajectories of T-cell differentiation and fate. However, these metabolic events of T cells could be dysregulated by their interplays with tumor or the tumor microenvironment (TME). Importantly, metabolic competition in the tumor ecosystem is a new mechanism resulting in strong suppression of effector T cells. It is appreciated that targeting metabolic reprogramming is a promising way to disrupt the hypermetabolic state of tumor cells and enhance the capacity of immune cells to obtain nutrients. Furthermore, immunotherapies, such as adoptive cell therapy (ACT) and immune checkpoint inhibitor (ICI), oncolytic virus (OV) therapy, have significantly refashioned the clinical management of solid tumors, they are not sufficiently effective for all patients. Understanding how immunotherapy affects T cell metabolism provides a bright avenue to better modulate T cell anti-tumor response. In this review, we provide an overview of the cellular metabolism of tumor and T cells, provide evidence on their dynamic interaction, highlight how metabolic reprogramming of tumor and T cells regulate the anti-tumor responses, describe T cell metabolic patterns in the context of ICI, ACT, and OV, and propose hypothetical combination strategies to favor potent T cell functionality.